Bacteriotherapy in Breast Cancer - Yaghoubi, Atieh (Int J Mol Sci, 2019)
Breast cancer is the second most common cause of cancer-related mortality among women around the world. Conventional treatments in the fight against breast cancer, such as chemotherapy, are being challenged regarding their effectiveness. Thus, strategies for the treatment of breast cancer need to be continuously refined to achieve a better patient outcome. We know that a number of bacteria are pathogenic and some are even associated with tumor development, however, recent studies have demonstrated interesting results suggesting some bacteria may have potential for cancer therapy. Therefore, the therapeutic role of bacteria has aroused attention in medical and pharmaceutical studies. Furthermore, genetic engineering has been used in bacterial therapy and may led to greater efficacy with few side effects. Some genetically modified non-pathogenic bacterial species are more successful due to their selectivity for cancer cells but with low toxicity for normal cells. Some live, attenuated, or genetically modified bacterias are capable to multiply in tumors and inhibit their growth. This article aims to review the role of bacteria and their products including bacterial peptides, bacteriocins, and toxins for the treatment of breast cancer.